Feasibility study of adoption of network expansion strategies by mobile service providers in North East India : a case study of Aircel Limited - Sarma, Rajkumar; Badir, Yuosre; Kumar, Arun; Winai Wongsurawat; ADB-Japan Scholarship Program (ADB-JSP) (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
The growth of the telecom industry in India ha s been on an exponential trajectory since the liberalization of the telecom sector in 1994, driven primarily by the proliferation of cellular mobile industry. India with over 200 million telephone connections with an addition of 6 million new connections every month is today the fastest growing mobile market in the world. Expansion of the mobile networks by respective service providers is now being regarded as prime key in sustaining this growth path. This implies adding of more subscribers by means of additional investme nts in building infrastructure like deploying more towers etc as means of network expansion. However, the high costs of rolling out network expansion are emerging as a major burden upon the service providers for faster and efficient network expansion. CAPEX (Cap ital Expenditure) into network expansion accounts for the single biggest cash flow expenditure for service providers while two thirds of that actually goes in to infrastructure costs. Passive infrastructure like towers, repeaters, shelters and generators account s for as much as 60 percent of the total network roll-out cost. The total investment in to infrastructure is actually multiplied several times over because of network duplication by each operator. These high investments into network expansion have resulted in lower ARPU (A verage Revenue Per User) for most of the mobile service providers as reflected in their recent financial results. Hence there is a need for the mobile service providers today to explore, study, know and implement various combined strategies for network expansion rath er than sticking to old conventional ways of network expansion which are not only cash but also time consuming. This study is aimed at exploring and then developing a model in implementing various network expansion strategies possible for a mo bile service provider (Aircel Ltd. for the scope of this study) in the North Eastern region of India. This research study is targeted at developing a right way in choosing different strategies for network expansion under different policy regions and also under differen t conditions of network expansion. Finally a right set of strategies for network expansion, as selected based upon a thorough cost- benefit analysis, are to be suggested to Aircel Ltd. for each of the three telecom circles in North East of India. It has been found from the results of this study that there are six different types of network expansion strategies available to be adopted for Aircel Ltd. and implement them strategically in the three telecom circles of North East India. A thorough cost-benefit analysis has been done and it has been found that new strategies for network expansion that are aimed at sharing infrastructure among mobile service providers or the strategies that involve independent infrastructure companies providing ready to use mobile infrastructure to mobile operators are high on benefits and low on cost. With government policies completely supporting infrastruct ure sharing and releasing licenses for independent tower vendors, adopting these strategies can not only save a lot of CAPEX for Aircel but can also dramatically reduce time to market. Overall these savings and benefits can reflect with the increasing ARPU levels in future. However, not every strategy may be possible to adopt at ease or will as some po licy or operating condition constraint may come up and hence this research study has come up with a detailed decision making steps on a flow chart basis for Aircel Ltd. to choose the best network expansion strategy under the given policy and conditions of network operation.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration in Business Administration {u2013}MBA
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2010
Submitted in partial fulfillment of the requirements for the degree of Master of Business Administration in Business Administration
Keywords: Telecommunication -- India; Cellular telephone services industry -- India